Macroeconomic Impacts of FDI Inflows: An Empirical Analysis from South Africa - Adekunle, Ahmed Oluwatobi (International Journal of Economics and Financial Issues, 2025)
This study evaluates macroeconomic impacts of FDI inflows on South Africa (SA) economy. The study employed Johansen cointegration test, block exogeneity test and Vector Error Correction Model (VECM) to evaluate the variables spanning over 1986-2021. It has been demonstrated that there is a unidirectional causal relationship between export and economic growth, an increase in exports (EXP) causes a rise in SA's economic growth. Economic growth and REXR were found to be causally related, indicating that higher Real Exchange Rate (REXR) values correspond to higher economic growth. Moreover, there is no correlation between FDI inflows and economic expansion. On the other hand, looking at the non-significant levels between External debt (EXTD) and CGDP indicates that the stock of external debt does not drive growth in SA. The study recommends a standardized export agency should be established to oversee the exportable units, their quality, and the standardization of goods and services, necessitating the implementation of an efficient export policy.